2015
DOI: 10.1371/journal.pone.0142344
|View full text |Cite
|
Sign up to set email alerts
|

A Unifying Organ Model of Pancreatic Insulin Secretion

Abstract: The secretion of insulin by the pancreas has been the object of much attention over the past several decades. Insulin is known to be secreted by pancreatic β-cells in response to hyperglycemia: its blood concentrations however exhibit both high-frequency (period approx. 10 minutes) and low-frequency oscillations (period approx. 1.5 hours). Furthermore, characteristic insulin secretory response to challenge maneuvers have been described, such as frequency entrainment upon sinusoidal glycemic stimulation; substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…Moreover, individuals with isolated IGT also showed a severely diminished second-phase insulin secretory response [ 5 , 6 ]. However, a recent study proposed a mathematical model of pancreatic insulin secretion that is in disagreement with the above reports [ 7 ]. In insulin resistance associated with prediabetes, the insulin secretory response increases as a compensatory mechanism.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, individuals with isolated IGT also showed a severely diminished second-phase insulin secretory response [ 5 , 6 ]. However, a recent study proposed a mathematical model of pancreatic insulin secretion that is in disagreement with the above reports [ 7 ]. In insulin resistance associated with prediabetes, the insulin secretory response increases as a compensatory mechanism.…”
Section: Introductionmentioning
confidence: 78%
“…Firstly, appropriately designed clinical trials aiming at evaluating variations in oscillatory patterns in subjects at various diabetic states under glucose infusions would be of great value. Secondly, new multiscale simulations taking into account dynamics at the β-cell secretion level as performed in [4] in the case of decreased insulin sensitivity could lead to a further assessment of the current model against clinical observations. Moreover, we have shown that taking into account an instantaneous glucose-dependent insulin production, through the introduction of an additional coefficient, enables us to characterise the existence of sinusoidal solutions by investigating roots of a cubic polynomial.…”
Section: Discussionmentioning
confidence: 99%
“…The islet equations are coupled to a metabolism sub-model to complete the description of the feed-back control of the glucose/insulin system dynamics. This islet population model was shown to reproduce very closely a wide array of actually observed, diverse in vivo and in vitro experiments, including the pioneering work of Grodsky, with the same set of working parameters [17]. While the model does not include any dependency on the rate of change of glycemia, it is able to reproduce accurately the double phase of insulin release during a prolonged glucose stimulus: a first phase of impulsive insulin release, immediately upon glucose administration, and a second phase of more gradual release, also linked with the potentiation effect of persistent hyperglycemia on the secretory units.…”
Section: Introductionmentioning
confidence: 98%
“…Now, a few years after the publication of the SDM model, a comprehensive model for insulin secretion exists [15, 17], which is in fact able to explain mechanistically why a host of morphologically diverse insulin secretion responses to glycemic perturbations occur. We can therefore go back and attempt to understand why the nonlinearity γ was so essential in the representation of insulin secretion within the compact SDM model: this is the aim of the present work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation